Kajian Literatur tentang Dimensi Lengkung Gigi Fase Gigi Bercampur pada Anak Laki-Laki dan Perempuan - Puspita Hadi; Ryna Dwi Yanuaryska; Sri Kuswandari (Syntax Corporation Indonesia, 2024)
The tooth growth phase starts from the age of 6 years with the first molar growth, this is a reference to assess the need for space and the possibility of malocclusion in adulthood. The dimension of the tooth arch is important in orthodontic treatment in children, especially in the mixed teeth phase because it will affect the treatment plan. The dimensions of the tooth arch are affected by various factors such as tooth eruption, genetics, growth patterns, environment and ethnicity. This study is a Literature Review using secondary databases from Google Scholar, Science Direct and Pubmed with the keywords